MAKNA SIMBOLIK RUMAH ADAT FOLAJIKO SARABI TIDORE - Rahmat Rahmat (Komunitas Dosen Dakwah Institut Agama Islam Negeri (IAIN) Palu, 2020)
The traditional house of Folajiko Sarabi is closely related to the Tidore Sultanate, which is the Islamic Kingdom, which is one proof of Islamic civilization in the past, and its existence still exists today. The results of this study indicate that the architectural construction of thetraditional house is folajiko sarabi divided into three parts, namely (1) the construction of the top, likened to the human head which is the highest and most important part of its role in the structure of the human body. the shape of the roof of the traditional house of Folajiku Sarabi is triangular in shape like the hat of Sultan Tidore which is known as besu. (2) The construction of the middle is likened to the human body. In this part of the body there is a Jaro, which is a whole bamboo pole that is attached by means of the base of the bamboo at the bottom and the tip is above, which means a living creature created by Allah that grows alive on the ground. (3) The construction of the lower part is likened to a human leg that must be able to support it in any condition. In this section, there is a hang, which means a large bamboo base or foundation on which thesupported jaro is. In this part of the foot, there is a hale or land as a floor, land also means prosperity, because most living things depend on crops or land as a source of livelihood.